Research on Boundary Layer Effect in Fractured Reservoirs Based on Pore-Scale Models - Wang, Deqiang; Zhang, Xiansong; Zhang, Jian (Frontiers in Earth Science, 2021)
It is of great significance to study the seepage characteristics of heavy oil reservoirs, which are conducive to the efficient development of resources. Fluid-solid interaction (FSI) exists in the pore scale flow process of macromolecular fluid media, which is different from the flow law of conventional fluid in the pore, yet the influence of FSI is ignored in the previous pore-scale simulation. Conventional porous media simulations have difficulty analyzing the mass transfer law of small-scale models under the influence of microfractures. Based on the CT scanning data and thin section data of the real core in the target area, the rock skeleton and flow space were extracted according to the maximum ball algorithm, and the pore network model representing the complex structure was constructed. The microscale effect of macromolecules in the flow process in the pores was characterized by modifying the effective flow. The effects of the FSI on the effective connectivity, displacement process and oil distribution law were analyzed. The seepage characteristics of different wettability conditions and different water cut stages were compared. The results show that FSI reduces the effective flow space and leads to deviations in the relative permeability curve and capillary curve. For fractured porous media, the irregular shape of porous media was characterized by morphological method and the mass transfer process was analyzed by the equivalent flux method. The influence of porous media shape on the macro mass transfer process was compared. This study provides a solution to the problem of FSI in pore scale simulation.